Decision support systems : issues and challenges : proceedings of an international task force meeting, June 23-25, 1980 - Fick, Goran; Sprague, Ralph H. (IIASA proceedings series, 1980)
Decision Support Systems: Issues and Challenges covers the proceedings of the International Institute for Applied Systems Analysis (IIASA) International Task Force Meeting. The book reviews papers that tackle issues about decision support systems (DSS). Comprised of 17 chapters, the book organizes the chapters according to the topic of discussion, including framework, resource discipline, application experience, and issues for the future in DSS. The opening chapter is an introduction to the main topic of the book. Chapter 2 discusses frameworks for research on decision support systems, and Cha.